(untitled) (Journal of Applied Membrane Science & Technology, 2024)
The rapid growth of the population and industrial development have led to a significant increase in wastewater generation across various sectors. The textile industry stands out as a major contributor to economic growth but also a substantial source of environmental pollution. The typical effluents discharged from textile industries are a complex mixture of dyes, metals, and other pollutants. The presence of high levels of pollutants may overwhelm traditional treatment methods. Therefore, it is necessary to use more advanced techniques such as membrane filtration to treat the wastewater. Membrane technology has recently become famous for wastewater treatment due to its flexibility, high efficiency in removing contaminants, and low energy usage. There are several membrane filtration methods which are extensively used in water treatment procedures, including microfiltration (MF), ultrafiltration (UF), nanofiltration (NF), and reverse osmosis (RO). In this study, the membrane process investigated the effect of feed pressure using a commercial MF flat sheet membrane on the performance of treatment. The pressure of the feed varies from 2 to 10 bar, with a stepwise increment of 2 bar. The water flux was measured using a cross-flow filtration system, and performance was assessed by calculating the water flux and removal efficiencies for total suspended solids (TSS) and turbidity. The results show that the MF membrane has a high removal efficiency of total suspended solids and turbidity. The removal efficiency of TSS ranged from 87.1% to 96.2%, while the removal efficiency of turbidity ranged from 91.2% to 93.7%.